Kiss of crimson eaudiobook - Adrian, Lara (Midnight Breed, 2010)
He comes to her more dead than alive, a towering black-clad stranger riddled with bullets and rapidly losing blood. As she struggles to save him, veterinarian Tess Culver is unaware that the man calling himself Dante is no man at all but one of the Breed, vampire warriors engaged in a desperate battle. In a single erotically charged moment, Tess is plunged into his world—a shifting, shadowed place where bands of Rogue vampires stalk the night, cutting a swath of terror. Haunted by visions of a dark future, Dante lives and fights like there is no tomorrow. Tess is a complication he does not need—but now, with his brethren under attack, he must shield Tess from a growing threat that includes Dante himself. For with one reckless, irresistible kiss, she has become an inextricable part of his underworld realm...and his touch awakens her to hidden gifts, desires, and hungers she never knew she possessed. Bonded by blood, Dante and Tess must work together to thwart deadly enemies, even as they discover a passion that transcends the boundaries of life itself.